(untitled) (Orinoquia, 2016)
In livestock farms, cattle are exposed to different stressors from growth to slaughter, affecting the welfare and temperament of animals. The term "temperament" is defined as the reaction produced by an animal in the presence of man and is affected by various factors such as breed, gender, age, management and genetics. During the evaluation of cattle temperament, animals with an excitable temperament (nervous) tend to have high scores on assessments of pen, chute and chute exit velocity, which are associated with high concentrations of glucocorticoids and catecholamines. Also, animals with nervous temperament have low daily gains (slow growth) and lower results of carcass and meat quality compared to animals with calm temperament. The purpose of this paper is to review the relationship between temperament and beef cattle production.